Glacier as a source of novel polyethylene terephthalate hydrolases - Qi, Xiaoyan; Ji, Mukan; Yin, Chao‐Fan; Zhou, Ning‐Yi; Liu, Yongqin (Environmental microbiology, 2023)
Polyethylene terephthalate (PET) is a major component of microplastic contamination globally, which is now detected in pristine environments including Polar and mountain glaciers. As a carbon‐rich molecule, PET could be a carbon source for microorganisms dwelling in glacier habitats. Thus, glacial microorganisms may be potential PET degraders with novel PET hydrolases. Here, we obtained 414 putative PET hydrolase sequences by searching a global glacier metagenome dataset. Metagenomes from the Alps and Tibetan glaciers exhibited a higher relative abundance of putative PET hydrolases than those from the Arctic and Antarctic. Twelve putative PET hydrolase sequences were cloned and expressed, with one sequence (designated as GlacPETase) proven to degrade amorphous PET film with a similar performance as IsPETase, but with a higher thermostability. GlacPETase exhibited only 30% sequence identity to known active PET hydrolases with a novel disulphide bridge location and, therefore may represent a novel PET hydrolases class. The present work suggests that extreme carbon‐poor environments may harbour a diverse range of known and novel PET hydrolases for carbon acquisition as an environmental adaptation mechanism. Qi et al. identified 414 genes of potential Polyethylene terephthalate (PET) hydrolases from metagenomes of global glaciers. By cloning and expression in E. coli, one enzyme demonstrated evident activity against PET. This enzyme, designated as GlacPETase is mesophilic and harbours a single disulphide bridge at the N‐terminus. This work revealed the potential of obtaining novel PET degradation enzymes from glacier environment.